Positivity in Younger and in Older Age: Associations With Future Time Perspective and Socioemotional Functioning - Erbey, Miray; Roebbig, Josefin; Babayan, Anahit; Kumral, Deniz; Reinelt, Janis; Reiter, Andrea M. F.; Schaare, Lina; Uhlig, Marie; Nierhaus, Till; Van der Meer, Elke; Gaebler, Michael; Villringer, Arno (Frontiers in Psychology, 2020)
Aging has been associated with a motivational shift to positive over negative information, which is often explained by a limited future time perspective (FTP) within the framework of socioemotional selectivity theory (SST). However, whether a limited FTP functions similarly in younger and older adults, and whether inter-individual differences in socioemotional functioning are similarly associated with preference for positive information (i.e., positivity) in both groups is still not clear. We investigated younger (20 to 35 years, N = 73) and older (60 to 75 years, N = 56) adults’ gaze preferences on pairs of happy, angry, sad, and neutral faces using an eye-tracking system. While we found no age-related differences in positivity when the entire trial duration was considered, older adults showed longer fixations on the more positive face in later stages of processing (positivity shifts). This allocation of resources towards more positive stimuli might serve an emotion regulatory purpose and seems consistent with the SST. However, our findings suggest that FTP differentially relates to positivity such that the relationship between FTP and positivity was negative in older, and positive in younger adults. Furthermore, our explanatory analyses showed that between-person differences in positivity and FTP differentially relate to proxies of socioemotional functioning such as stress, social support, cognitive functioning, emotion regulation, and well-being across age. In conclusion, we confirm the existence of positivity effect, and show a differential relevance of FTP for positivity in younger and older adults stemming from a differential meaning of FTP construct across age.